2021
DOI: 10.3390/ijms22105260
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein Coupled Receptors (GPCRs): Signaling Pathways, Characterization, and Functions in Insect Physiology and Toxicology

Abstract: G-protein-coupled receptors (GPCRs) are known to play central roles in the physiology of many organisms. Members of this seven α-helical transmembrane protein family transduce the extracellular signals and regulate intracellular second messengers through coupling to heterotrimeric G-proteins, adenylate cyclase, cAMPs, and protein kinases. As a result of the critical function of GPCRs in cell physiology and biochemistry, they not only play important roles in cell biology and the medicines used to treat a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 178 publications
1
28
0
Order By: Relevance
“…The value of the findings summarized in this review of the current status of research into GPCR in insects, including information on their sequences, functions in physiology and toxicology and the tissues and organs that they are involved in, are fundamental for understanding how these GPCR systems function to modulate a broad spectrum of cellular activities. A recent review on insect GPCRs uncovered GPCR signaling pathways, functions in insect physiology and toxicology and the latest exciting technological advances and new techniques for gene expression and functional of the GPCRs in insects [167]. Together, these reviews on insect GPCRs will help researchers in the field develop new insect-specific insecticides that will help control insect pests in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the findings summarized in this review of the current status of research into GPCR in insects, including information on their sequences, functions in physiology and toxicology and the tissues and organs that they are involved in, are fundamental for understanding how these GPCR systems function to modulate a broad spectrum of cellular activities. A recent review on insect GPCRs uncovered GPCR signaling pathways, functions in insect physiology and toxicology and the latest exciting technological advances and new techniques for gene expression and functional of the GPCRs in insects [167]. Together, these reviews on insect GPCRs will help researchers in the field develop new insect-specific insecticides that will help control insect pests in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that G‐protein‐coupled receptor (GPCR) regulation pathways play key roles in insect physiological processes, toxicological responses and the development of insecticide resistance. The GPCR regulation pathway regulates P450 gene expression and P450‐mediated insecticide resistance by activating downstream effectors, such as heterotrimeric G‐proteins, adenylate cyclase (AC), protein kinase A (PKA), and cyclic adenosine 3′,5′‐monophosphate (cAMP) 32–36 . The ligand adipokinetic hormone (AKH) synthesized and released by the corpora cardiaca (CC) and AKH receptor (AKHR) as rhodopsin‐like GPCR has been proven to be involved in the regulation of energy metabolism, feeding, reproduction, diapause, flight and other activities.…”
Section: Introductionmentioning
confidence: 99%
“…The GPCR regulation pathway regulates P450 gene expression and P450-mediated insecticide resistance by activating downstream effectors, such as heterotrimeric G-proteins, adenylate cyclase (AC), protein kinase A (PKA), and cyclic adenosine 3 0 ,5 0 -monophosphate (cAMP). [32][33][34][35][36] The ligand adipokinetic hormone (AKH) synthesized and released by the corpora cardiaca (CC) and AKH receptor (AKHR) as rhodopsin-like GPCR has been proven to be involved in the regulation of energy metabolism, feeding, reproduction, diapause, flight and other activities. Particularly under stress conditions, AKH and AKHR can couple and participate in antioxidant stress responses by activating AC, PKA and cAMP.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of adrenergic receptors (which are approximately divided into α1, α2, and β receptors) requires the mediation of G protein to couple with the second messenger to produce a series of signal transduction and physiological effects. 24 , 25 In contrast to the effect of β receptors in increasing the concentration of cAMP in smooth muscle cells by coupling to Gs, α2 receptors couple with Gi, which can inhibit the activity of adenylate cyclase and reduce the synthesis of cAMP, thereby reducing MLCK activity inhibition with the result of smooth muscle cell contraction. 26–28 Some studies concerning the relationship between cervical tone and adrenergic receptors also support the abovementioned discussion.…”
Section: Discussionmentioning
confidence: 99%